Fungi Identification in Preservative Liquids of Cadaver at Anatomy Laboratory of Faculty of Medicine Maranatha Christian University Bandung - Mochamad H. Herdiman; Triswaty Winata; Tediany Pramesti; Imam G. Alam (Journal of Medicine and Health, 2018)
Cadaver is an important learning media for students of the Faculty of Medicine. Althoughthe cadaver has undergone a preservation process, sometimes the preservative liquids used onlyprotects the cadaver, and does not inhibit the fungal growth. Based on previous research, thefungus found in cadaveric preparations are pathogenic. The objectives of this study were toidentify the growing fungus on the cadaver preservative liquid at the Anatomy Laboratory of theFaculty of Medicine, Maranatha Christian University. This is a descriptive experimental study.Samples were taken from three cadaver tubs. Subsequently, the sample was inoculated onSabouraud's Dextrose Agar and Chromagar medium in a petridish and incubated at roomtemperature (25 â° ) for seven days. After seven days, the morphology of the fungus was observedmacroscopically and microscopically. We found Aspergillus sp., Penicillium sp.,Epidermophyton sp., and Candida sp on the samples. The study was conducted in December2017-January 2018 at the Microbiology Laboratory, Faculty of Medicine, Maranatha ChristianUniversity and Microbiology Laboratory, Faculty of Medicine, Padjadjaran University.Keywords: fungi, cadaver, preservative liquid